Assessment of investments in education impact on the Russian regional economic stability - V. V. Stroev (Вестник университета)
The study assesses the public and private investment in education impact on the economic stability level in the Russian regions. The paper is based on the hypothesis of the key role of educational infrastructure development in the sustainable regional economy formation. The direct correlation between the population’s educational level and the dynamics of gross regional product, investment activity and territorial innovative development has been analyzed. The influence degree of investments in the highly qualified personnel training on the unemployment reduction, growth of average per capita income of citizens, knowledge-intensive economy sectors development has been assessed. The study is based on the analysis of the Federal State Statistics Service of the Russian Federation data, review of regional budgets for 2020–2022 and expert surveys among economists and educational workers. The correlation and regression analysis methods were applied to determine the relationship between the investment in education volume and regional economic stability indicators. The preliminary study results indicate a significant investment in education impact on the regional economic stability. In particular, the regions with higher investments in the educational sphere have lower unemployment rates, higher average income per capita and higher level of enterprises’ innovative activity.